Report of Guyana on the development of education, 1978-1980 - Guyana. Ministry of Education, Social Development and Culture
This official report from Guyana for the 1981 International Conference on Education (ICE) summarized educational organization and highlighted major educational developments. Significant innovations in preprimary education included the training of Nursery Education Leaders and a three-year inservice training programme for nursery teachers. Remedial instruction was given to slow learners and low achievers in primary and secondary schools. The Work-Study Programme was extended quantitatively and qualitatively through the introduction of prevocational and vocational subjects at Community High Schools and Multilateral Schools. In 1980, a new Ministry of Higher Education was established, taking over the responsibility for technical and higher education. Developments in educational research are mentioned
Keywords: Educational organization